Engineering students’ use of technical literature in English and attitudes towards ESP - Jelena Hodak; Brankica Bošnjak Terzić (Strani Jezici, 2023)
Considering the rapid development of science and technology and the fact that a vast majority of scientific and professional papers are published in English, it is necessary to be proficient in English in order to be able to keep abreast of the most recent developments in the field. The aim of this study was to gain insight into how much the students of the Faculty of Mechanical Engineering and Naval Architecture, University of Zagreb, Croatia, use technical literature in English (TLE) for study purposes and whether TLE use is related to students’ attitudes to English for specific purposes (ESP) in three contexts: university study, professional development, and career advancement. The study was conducted using an online survey created by the authors. The participants were 533 Engineering students (394 male and 139 female) from all years of study. The results showed that students use TLE rarely to moderately. Curricular requirements appear to be the strongest factor leading to TLE use, while positive attitudes towards the importance of ESP proficiency and ESP proficiency itself seem to be facilitating factors for more frequent TLE use.